High hepatitis B seroprevalence and risk factors for infection in pregnant women on the Thailand-Myanmar border - Banks, T; Khang, J; Watts, I; Tyrosvoutis, M; Min, A; Tun, N; Keereecharoen, L; Simmawong, W; Wanyatip, S; Hanboonkunupakarn, B; Nosten, F; Mcgready, R (Journal of Infection in Developing Countries, 2016)
Introduction: Infection from Hepatitis B primarily results from peri-partum vertical transmission and the risk increases in the presence of hepatitis B e antigen. We aimed to evaluate a new screening program for hepatitis B in pregnant women as a component of antenatal services in a marginalized population.